Inhibition of peroxidase activity and scavenging of reactive oxygen species by astilbin isolated from Dimorphandra mollis (Fabaceae, Caesalpinioideae) - Petacci, Fernando; Freitas, Silvia S.; Brunetti, Iguatemy L. [UNESP]; Khalil, Najeh M. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2010)
Astilbin (5,7,3',4'-tetrahydroxy-2,3-dihydroflavonol-3-β-o-rhamnoside), a flavonoid with a large range of biological activities, was isolated from Dimorphandra mollis, a shrub common to the Brazilian Cerrado. The purpose of this study is to verify the effects of astilbin on myeloperoxidase (MPO) and horseradish peroxidase (HRP), and its antioxidant activity against hypochlorous acid (HOCl) and total antioxidant activity (TAC) by the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS•+). Astilbin inhibited MPO and HRP activities in a concentration-dependent relationship and effectively scavenged HOCl. The TAC by ABTS•+ of astilbin (IC50 ~ 20 mM) was higher than that of uric acid, which was used as a positive control. These data demonstrate that astilbin is a potent antioxidant and that it inhibits MPO and HRP activities efficiently.
Keywords: Astilbin; Horseradish peroxidase; Hypochlorous acid; Myeloperoxidase; Reactive oxygen species